2012
DOI: 10.1068/d3006pan
|View full text |Cite
|
Sign up to set email alerts
|

Geopower: A Panel on Elizabeth Grosz's Chaos, Territory, Art: Deleuze and the Framing of the Earth

Abstract: Rather than understand art as cultural accomplishment, Elizabeth Grosz argues that it is born from the intensities of chaos and disruptive forms of sexual selection—a corporeality that vibrates to the hum of the universe. Grosz contends that it is precisely this excessive, nonproductive expenditure of sexual attraction that is the condition for art's work. This intimate corporeality, composed of nonhuman forces, is what draws and transforms the cosmos, prompting experimentation with materiality, sensation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(40 citation statements)
references
References 7 publications
0
40
0
Order By: Relevance
“…However, just as the Anthropocene conceptually enables us to think biopower as it produces landscape, it also enables us to see human landscapes 'in another sense, they are an entirely novel and quite gargantuan trace fossil system, one that extends kilometres deep into older rock in the form of millions of boreholes and mineshafts' thus, human history must be seen 'within the deep-time context of the rock record' (Zalasiewicz, 2013). Ultimately the politics of writing history (de Certeau, Page | 10 1988) is undermined through an account of thinking geopower (Yusoff et. al.…”
Section: The Possibilities For Democratic Politicsmentioning
confidence: 99%
“…However, just as the Anthropocene conceptually enables us to think biopower as it produces landscape, it also enables us to see human landscapes 'in another sense, they are an entirely novel and quite gargantuan trace fossil system, one that extends kilometres deep into older rock in the form of millions of boreholes and mineshafts' thus, human history must be seen 'within the deep-time context of the rock record' (Zalasiewicz, 2013). Ultimately the politics of writing history (de Certeau, Page | 10 1988) is undermined through an account of thinking geopower (Yusoff et. al.…”
Section: The Possibilities For Democratic Politicsmentioning
confidence: 99%
“…In this much, there are important resonances between Latour's work and that of Elizabeth Grosz whose writings have, to date, provided the principal philosophical inspiration for 'rethinking the geo-' in political geographical debates (e.g. Yusoff et al 2012). However, Grosz's political ontology is, from Latour's perspective, unacceptable in that it defines politics in terms of power.…”
Section: Global Discourse 21mentioning
confidence: 86%
“…This paper has suggested that an important aspect of understanding the geosocial might be around its commodification, through experiences of active and dynamic landscapes as well as through art and culture (Dixon et al., ; Grosz, ; Yusoff et al., ): people are drawn to the sensory and imaginative, knowledge‐generating spectacles of volcanic eruptions because of their affective and personal effects. Such encounters enrich curiosity – several survey respondents stated that the eruption in 2010 had inspired them to study geoscience – and they change the way that people think – in a sense consistent both with Deleuze and with notions of the sublime as simultaneously showing mental limits and pointing beyond them.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in the geohumanities has sought to re‐engage with the Earth as a source of inspiration, energy and philosophy (Clark, ; Palsson & Swanson, ; Yusoff et al., ). Grosz () used the notion of “geopower” to understand the interactions between the forces of the earth and the human.…”
Section: Introductionmentioning
confidence: 99%